Aquifer Storage and Recovery Feasibility Study With Flowing Fluid Electrical Conductivity Logging in Shallow Aquifers of South Bihar, India - Verma, Anurag; Sharma, Prabhakar (Frontiers in Water, 2022)
Growing dependence on groundwater to fulfill the water demands has led to continuous depletion of groundwater levels and consequently poses the maintenance of optimum groundwater and management challenge. The region of South Bihar faces regular drought and flood situations, and due to the excessive pumping, the groundwater resources are declining. Rainwater harvesting has been recommended for the region; however, there are no hydrogeological studies concerning groundwater recharge. Aquifer storage and recovery (ASR) is a managed aquifer recharge technique to store excess water in the aquifer through borewells to meet the high-water demand in the dry season. Therefore, this paper presents the hydrogeological feasibility for possible ASR installations in shallow unconfined aquifers of South Bihar with the help of flowing fluid electrical conductivity (FFEC) logging. For modeling, the well logging data of two shallow borewells (16 m and 47 m depth) at Rajgir, Nalanda, were used to obtain the transmissivity and thickness of the aquifers. The estimated transmissivities were 804 m2/d with an aquifer thickness of 5 m (in between 11 m to 16 m) at Ajatshatru Residential Hall (ARH) well. They were 353 m2/d and 1154 m2/d with the aquifer thicknesses of 6 m (in between 16 m to 22 m) and 2 m (in between 45 m to 47 m) respectively at Nalanda University Campus (NUC) well. Despite the acceptable transmissivities at these sites, those aquifers may not be fruitful for the medium to large scale (more than 100 m3/d injection rate) ASR as the thickness of the aquifers is relatively small and may not efficiently store and withdraw a large amount of water. However, these aquifers can be adequate for small (up to 20 m3/d injection rate) ASR, for example, groundwater recharge using rooftop water. For medium to large-scale ASR, deeper aquifers need to be further explored on these sites or aquifers with similar characteristics.